VD_FINDINFO 15/2015 vom 2. Juni 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, DROIT À UNE AUTORITÉ INDÉPENDANTE ET IMPARTIALE | 6 ROTC, 47 al. 1 let. f CPC (CH), 47 CPC (CH), 48 CPC (CH), 8a al. 3 CDPJ, 8a CDPJ, 8b al. 4 CDPJ